2023
DOI: 10.14202/vetworld.2023.1477-1488
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of herbal plants on rumen fermentation, methane gas emissions, in vitro nutrient digestibility, and population of protozoa

Antonius Antonius,
Roni Pazla,
Ezi Masdia Putri
et al.

Abstract: Background and Aim: Herbal plants have the potential to reduce the population of metagonic bacteria and protozoa due to the bioactive compound contained in herbal plants. This study aimed to evaluate the effect of herbal plant supplementation on rumen fermentation characteristics, methane (CH4) gas emissions, in vitro nutrient digestibility, and protozoan populations. Materials and Methods: This study consisted of two stages. Stage I involved determining the potential of herbal plants to increase total gas pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…The pattern of OMD is linear with DMD because it constitutes the largest component of DM. This linear pattern has been previously observed by Antonius et al (2023); Elihasridas et al (2023a). The organic material components in the A1B2 treatment are more easily degraded by rumen microbes, resulting in higher OMD than other treatments.…”
Section: Digestibility Of Dry Matter Organic Matter and Crude Proteinsupporting
confidence: 83%
“…The pattern of OMD is linear with DMD because it constitutes the largest component of DM. This linear pattern has been previously observed by Antonius et al (2023); Elihasridas et al (2023a). The organic material components in the A1B2 treatment are more easily degraded by rumen microbes, resulting in higher OMD than other treatments.…”
Section: Digestibility Of Dry Matter Organic Matter and Crude Proteinsupporting
confidence: 83%
“…Gang et al [ 27 ] found that increased DM digestibility was followed by increased gas production with the addition of lactic acid bacteria inoculum. The gas produced during rumen fermentation is considered an indicator of rumen digestibility, which is related to DM and OM digestibility [ 28 , 29 ]. The in vitro digestibility and fiber fraction content of ADF and NDF in this study, as well as total gas production, align with the reports of previous studies [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to Antonius et al [14], an elevated breakdown of organic matter in the diet corresponds to increased nutrient sufficiency for livestock. The digestibility pattern of organic matter is similar to that of DM digestibility.…”
Section: Digestibility Of Dry Matter and Organic Mattermentioning
confidence: 99%